XBC battery slurry based on Ti, Cu and Cu-Ti alloy and preparation method of xBC battery slurry

By using slurries of Ti, Cu and Cu-Ti alloys in xBC batteries, combined with specific glass phases and auxiliary materials, the problem of difficult to take into account both the conductivity and manufacturing cost of the electrode is achieved, and efficient electrode performance and cost control are achieved.

CN119274844APending Publication Date: 2025-01-07JIANGSU RIYU PHOTOVOLTAIC NEW MATERIAL CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411314317.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The P-region electrode of xBC battery faces problems such as poor ohmic contact effect, large contact resistance and body resistance, and difficult to take into account both manufacturing cost and electrode performance, especially because the Al2O3+SiNx passivation film is difficult to corrode and the Al oxidation film affects the conductivity .

Method used

Using xBC battery slurry based on Ti, Cu and Cu-Ti alloys, composite Cu powder, composite Ti powder and Ag powder are used as the main body of conductive phases to reduce the Ag usage, and Cu-Ti alloy is introduced to reduce the melting point and improve the conductive performance. Through a specific combination of glass phase and auxiliary materials, the preparation method of the slurry is optimized to form efficient electrodes.

Benefits of technology

It significantly reduces the cost of electrode manufacturing, improves the ductility, strength and corrosion resistance of the electrode, and optimizes the conductivity, avoids the formation of Cu and Ti oxide films, and improves the overall performance of the electrode.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005051692640000071
    Figure BDA0005051692640000071
Patent Text Reader

Abstract

The invention relates to xBC battery slurry based on Ti, Cu and a Cu-Ti alloy. The xBC battery slurry comprises 85-90 wt% of a conductive phase; based on the total mass of the conductive phase, the conductive phase comprises 5-15 wt% of composite Ti powder, 10-30 wt% of composite Cu powder, 5-25 wt% of Cu-Ti alloy powder and 30-80 wt% of Ag powder; 3 to 6 wt% of a glass phase; 0.5 to 3 wt% of an auxiliary material; and the balance is a carrier. The invention also relates to a preparation method of the slurry, which comprises the following steps: S1, putting the solvent into a heating container, keeping the temperature at 50 DEG C, slowly adding the resin and stirring to form the organic carrier; s2, adding an auxiliary agent into the organic carrier, keeping the temperature at 50 DEG C, continuously stirring so that the auxiliary agent and the organic solvent are fully and uniformly mixed to form an auxiliary material, and then standing at room temperature for more than 12 hours for later use; s3, adding a glass phase and Ag powder into the auxiliary material, and stirring and dispersing; s4, Cu alloy powder is added into the auxiliary materials, stirring and dispersing are continued, and paste is obtained; and S5, uniformly dispersing the paste obtained in the step S4 to obtain the slurry.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of photovoltaic cells and conductive pastes, and in particular to an xBC cell paste based on Ti, Cu and Cu-Ti alloy and a preparation method thereof. Background Art

[0002] BC is the abbreviation of Back Contact, which means back-contact photovoltaic cells; there are many types of BC cells, such as PBC, IBC, HBC, etc., collectively referred to as xBC cells. Compared with existing TOPCon cells, HJT cells, etc., the biggest feature of xBC is that there is no grid line on the front, and the back is no longer a simple N area or P area, but usually a staggered P and N areas are prepared on the back of the battery, so that the positive and negative electrodes are integrated on the back of the battery. Thanks to this structure, there will be no electrode grid lines blocking the front of the xBC battery, which not only improves the power generation efficiency but also improves the aesthetics of the front. Because BC batteries adopt a design without metal grid lines on the front, the power generation per watt is usually about 2% to 3% higher than that of TOPCon batteries.

[0003] At present, the problem faced by the P-region electrode of xBC battery is that the ohmic contact effect is not good, the contact resistance and body resistance are both large, and it is difficult to balance the manufacturing cost and electrode performance; in addition, since N-type silicon wafers have a higher body life, they can ensure that the non-equilibrium carriers can smoothly reach the back pn junction area before recombination. Therefore, most BC batteries currently use N-type silicon wafers as substrates, and the Al2O3+SiN x The passivation film is difficult to corrode and the "window opening" effect is poor. In addition, in order to control the cost of slurry preparation, more Al and Ag are often co-doped. Although Al has good conductivity, the Al in the electrode is prone to produce Al2O3 oxide film and the finer Al powder is easy to agglomerate and difficult to disperse in the slurry system, which further affects the effect of ohmic contact. Summary of the invention

[0004] In order to solve the above problems, the present invention provides an xBC battery slurry based on Ti, Cu and Cu-Ti alloy and a preparation method thereof, which better balances the manufacturing cost and comprehensive performance of the xBC battery. The technical solution of the present invention is as follows:

[0005] In a first aspect, the present invention provides an xBC battery slurry based on Ti, Cu and Cu-Ti alloy, comprising:

[0006] 85-90wt% of a conductive phase; based on the total mass of the conductive phase, it includes 5-15wt% of composite Ti powder, 10-30wt% of composite Cu powder, 5-25wt% of Cu-Ti alloy powder, and 30-80wt% of Ag powder;

[0007] 3-6 wt% glass phase;

[0008] 0.5-3wt% auxiliary materials;

[0009] The remainder is carrier.

[0010] In one possible implementation,

[0011] The composite Ti powder is specifically a mixture of micron-sized flaky silver-coated Ti powder, micron-sized spherical silver-coated Ti powder, and nano-sized spherical silver-coated Ti powder; based on the total mass of the composite Ti powder, the content of the micron-sized spherical silver-coated Ti powder is 50-60wt%, and the content of the nano-sized spherical silver-coated Ti powder is not higher than 15wt%.

[0012] In one possible implementation,

[0013] The composite Cu powder is specifically a mixture of micron-sized flaky Cu powder, micron-sized spherical silver-coated Cu powder and nano-sized spherical silver-coated Cu powder; based on the total mass of the composite Cu powder, the content of the micron-sized flaky Cu powder is 30-40wt%, and the content of the nano-sized spherical silver-coated Cu powder is not higher than 5wt%.

[0014] In one possible implementation,

[0015] The Cu-Ti alloy powder is a mixture of micron-sized spherical Cu-Ti alloy powder, micron-sized flaky Cu-Ti alloy powder and nano-sized spherical Cu-Ti alloy powder;

[0016] In the Cu-Ti alloy, the content of Ti is 0.6-1.2 wt %.

[0017] In one possible implementation,

[0018] Based on the total mass of the Ag powder, it comprises 65-70wt% of micron-sized spherical Ag powder, 25-30wt% of micron-sized flaky Ag powder and 2-5% of nanometer-sized spherical Ag powder.

[0019] In a possible implementation, the glass phase includes a first glass powder and a second glass powder, and based on the total mass of the glass phase:

[0020] The first glass powder comprises 35-60 wt % of Bi2O3, 25-40 wt % of B2O3, and 5-20 wt % of SiO2;

[0021] The mass percentage of the second glass powder is 8-12wt%; the second glass powder is a mixture of at least two of BaO, ZnO, GaO, K2O, and Na2O.

[0022] In a possible implementation, the auxiliary material is a mixture of WO3, metal fluoride and boron powder; based on the total mass of the auxiliary material:

[0023] The content of WO3 is 30-50wt%;

[0024] The metal fluoride content is 10-15wt%;

[0025] The content of the boron powder is 30-45wt%; the D50 particle size of the boron powder is 1-2.5 μm.

[0026] In one possible implementation,

[0027] The carrier includes a mixed solvent and a resin;

[0028] The mixed solvent is a mixture of terpineol and butyl carbitol and / or citric acid, and the mass proportion of the terpineol is ≥60%;

[0029] Based on the total weight of the carrier, the resin comprises 5-8wt% of ethyl cellulose, 0-5wt% of Span series and / or Tween series, 1.5-2.5wt% of sodium dodecylbenzene sulfonate, and 0.2-0.8wt% of polyamide.

[0030] In a second aspect, the present application provides a method for preparing the above slurry, comprising the following steps:

[0031] S1. Place terpineol in a heating container, maintain the temperature at 45° C., slowly add butyl carbitol and / or citric acid and keep stirring, stir at a stirring speed of 15 rpm for 3 to 5 minutes, so that butyl carbitol and / or citric acid are fully mixed in terpineol to obtain a mixed solvent;

[0032] S2, mixing the various components of the resin evenly, keeping the mixed solvent at 45°C, adding the mixed resin to the mixed solvent, keeping the temperature at 50°C after the resin is completely added, and stirring continuously for 2.5 to 3 hours to make the resin and the mixed solvent fully mixed to form a liquid carrier with a uniform and stable texture, and cooling to room temperature for standby use;

[0033] S3, adding the glass phase and Ag powder into the carrier, stirring and dispersing at a speed of 20 to 30 rpm;

[0034] S4, stirring at a speed of 20 to 30 rpm, mixing the auxiliary materials and the Cu alloy powder evenly, and then adding them to the carrier, stirring continuously for 8 to 12 hours to obtain a paste;

[0035] S5. Disperse the paste obtained in S4 7 to 8 times, each time for 10 to 20 minutes, to obtain the slurry.

[0036] The above technical solution provided by this application has at least the following technical effects or advantages:

[0037] The xBC battery P-zone slurry disclosed in the present invention uses composite Cu powder, composite Ti powder and Ag powder as the main body of the conductive phase. First, the amount of Ag is reduced, thereby significantly controlling the manufacturing cost of the electrode slurry; second, Cu and other conductive base metals are distributed in the slurry system in the form of alloys, which, on the one hand, significantly reduces the melting point of the slurry and makes it easier to carry out the metallization process, and on the other hand, it is well avoided that metals such as Cu and Al produce oxide films during sintering and use, thereby affecting the conductive properties; in addition, some Cu-Ti alloys are introduced, so that the ductility, strength, corrosion resistance, etc. of the finished electrode are improved, and the manufacturing cost is further reduced without affecting the conductive effect. DETAILED DESCRIPTION

[0038] The specific implementation modes of the present invention are described below by way of examples.

[0039] Example 1

[0040] This embodiment provides an xBC battery slurry, including:

[0041] 85wt% of a conductive phase; based on the total mass of the conductive phase, it includes 5wt% of composite Ti powder, 10wt% of composite Cu powder, 5wt% of Cu-Ti alloy powder, and 80wt% of Ag powder;

[0042] 3wt% glass phase;

[0043] 1wt% of auxiliary materials;

[0044] The remainder is carrier.

[0045] Based on the total mass of the composite Ti powder, it includes:

[0046] 50wt% of micron-sized spherical silver-coated Ti powder, 40wt% of micron-sized flaky silver-coated Ti powder and 10wt% of nano-sized spherical silver-coated Ti powder;

[0047] Based on the total mass of the composite Cu powder, it includes:

[0048] 65wt% of micron-sized spherical silver-coated Cu powder, 30wt% of micron-sized flake Cu powder and 5wt% of nano-sized spherical silver-coated Cu powder;

[0049] Cu-Ti alloy powder is composed of alloy powders of different morphologies, including:

[0050] 65wt% of micron-sized spherical Cu-Ti alloy powder, 20wt% of micron-sized flake Cu-Ti alloy powder and 10wt% of nano-sized spherical Cu-Ti alloy powder; the Ti content in the Cu-Ti alloy is 0.6wt%;

[0051] Based on the total mass of the Ag powder, the Ag powder includes 65wt% of micron-sized spherical Ag powder, 30wt% of micron-sized flaky Ag powder and 5% of nanometer-sized spherical Ag powder.

[0052] The glass phase includes a first glass powder and a second glass powder, and according to the total mass of the glass phase:

[0053] The first glass powder comprises 35wt% Bi2O3, 35wt% B2O3, and 20wt% SiO2;

[0054] The mass percentage of the second glass powder is 10wt%; the second glass powder is a mixture of BaO, ZnO, GaO, K2O, and Na2O.

[0055] The auxiliary materials include: 40wt% WO3, 15wt% metal fluoride, and 45wt% boron powder; the metal fluoride can be CaF2, AlF3, NaF, etc., and the D50 particle size of the boron powder is 1-2.5μm.

[0056] The carrier includes a mixed solvent and a resin;

[0057] The mixed solvent is a mixture of terpineol, butyl carbitol and citric acid, and the mass proportion of terpineol is 70wt% based on the total mass of the mixed solvent;

[0058] Based on the total mass of the carrier, the resin includes 5wt% of ethyl cellulose, 5wt% of Span series and / or Tween series, 1.5wt% of sodium dodecylbenzene sulfonate, and 0.5wt% of polyamide.

[0059] Example 2

[0060] This embodiment provides an xBC battery slurry, the components of which are substantially the same as those of Embodiment 1, except that:

[0061] The conductive phase includes 10 wt % of composite Ti powder, 20 wt % of composite Cu powder, 15 wt % of Cu-Ti alloy powder, and 55 wt % of Ag powder.

[0062] Example 3

[0063] This embodiment provides an xBC battery slurry, the components of which are substantially the same as those of Embodiment 1, except that:

[0064] The conductive phase includes 10 wt % of composite Cu powder, 10 wt % of composite Ti powder, 25 wt % of Cu-Ti alloy powder and 55 wt % of Ag powder.

[0065] Example 4

[0066] This embodiment provides an xBC battery slurry, the components of which are substantially the same as those of embodiment 3, except that:

[0067] The conductive phase contains 10 wt % Cu-Ti alloy powder and 70 wt % Ag powder.

[0068] Example 5

[0069] This embodiment provides an xBC battery slurry, the components of which are substantially the same as those of embodiment 3, except that:

[0070] The conductive phase includes 5 wt % Cu-Ti alloy powder and 75 wt % Ag powder.

[0071] The preparation methods of the slurries of Examples 1 to 5 are basically the same, and all include the following steps:

[0072] S1. Place terpineol in a heating container, maintain the temperature at 45°C, slowly add butyl carbitol and citric acid and keep stirring, stir at a stirring speed of 15 rpm for 5 minutes to fully mix butyl carbitol and citric acid in terpineol to obtain a mixed solvent;

[0073] S2, mixing the various components of the resin evenly, keeping the mixed solvent at 45°C, adding the mixed resin to the mixed solvent, keeping the temperature at 50°C after the resin is completely added, and stirring for 3 hours to make the resin and the mixed solvent fully mixed to form a liquid carrier with a uniform and stable texture, and cooling to room temperature for standby use;

[0074] S3, adding the glass phase and Ag powder into the carrier, stirring and dispersing at a speed of 20 to 30 rpm;

[0075] S4, stirring at a speed of 20 to 30 rpm, mixing the auxiliary materials with the composite Ti powder, the composite Cu powder and the Cu-Ti alloy powder evenly, and then adding them to the carrier, stirring continuously for 10 hours to obtain a paste;

[0076] S5. Disperse the paste obtained in S4 8 times, each time for 10 to 20 minutes, to obtain the slurry.

[0077] Next, the slurries provided in Examples 1 to 5 are tested to illustrate the beneficial effects of the embodiments of the present application.

[0078] This experiment provides control groups 1 to 5. The slurry components and preparation methods of control groups 1 to 5 are basically the same as those of Example 1, except that:

[0079] Control group 1, whose conductive phase composition is 80wt% Ag powder, 10wt% Cu powder, and 10wt% Ti powder;

[0080] Control group 2, whose conductive phase composition is 75wt% Ag powder, 15wt% Cu powder, and 10wt% Ti powder;

[0081] Control group 3, whose conductive phase composition is 55wt% Ag powder, 25wt% Cu powder, and 20wt% Ti powder;

[0082] Control group 4, whose conductive phase composition is 75wt% Ag powder and 25wt% Cu-Ti alloy powder;

[0083] Control group 5, its conductive phase composition is 55wt% Ag powder and 45wt% Cu-Ti alloy powder.

[0084] Using screen printing technology, the slurries of Examples 1 to 5 and the slurries of Control Groups 1 to 5 were printed on silicon wafer substrates to form cells, which were dried in an infrared drying furnace, and then sintered at 740 to 800°C in a belt sintering furnace, and cooled after sintering to form silicon crystalline solar cells. After screen printing and sintering, the cross-sections of the metal grid lines of Examples 1 to 5 were close to Gaussian distribution. The line width was controlled at about 25 μm and the line height was about 5 μm.

[0085] For the prepared batteries, Examples 1 to 5 are designated as S1 to 5, and Control Groups 1 to 5 are designated as D1 to 5, and the contact resistance and line resistance are tested using a TLM contact resistance meter. The test results are shown in Table 1 below:

[0086] Table 1 - Electrical performance test of Examples 1 to 4 and Control Groups 1 to 6

[0087]

[0088]

[0089] By observing the appearance and cross-sectional micromorphology of the finished electrodes of S1 to S5, it is found that the micromorphology of the finished electrodes of S1 to S5 after sintering basically meets the requirements, and defects such as pores, cracks, and gaps are well controlled. This is because the base metals such as Cu and Ti are introduced in the form of alloys rather than in the form of single metals, which greatly reduces the melting point of the system and avoids the situation where high-melting-point metals such as Cu and Ti directly enter the system and cannot be fully melted and sintered.

[0090] From Table 1 we can see that:

[0091] After being sintered into electrodes, the slurries provided by S1 to S5 basically have relatively ideal line resistance and contact resistance performance. Among them, the electrical performance of S2 to S5 is slightly weaker than that of S1. It has been verified that this is because S1 has the highest Ag content and therefore has the best conductive performance.

[0092] The comprehensive performance of S2 and S3 is poorer than that of other embodiments. It has been verified that the main reason is that the Ag content in the system is too low and the Cu-Ti alloy content is high. The alloy will cause metal lattice distortion during the formation process, which will have a certain impact on the movement of electrons, and ultimately affect the electrical properties. Among them, S2 performs better than S3. It has been verified that the main reason is that more composite Cu powder is introduced. The micron-sized flaky Cu powder in the composite Cu powder plays the role of building a skeleton. On this basis, the micron-sized spherical silver-coated Cu powder and the nano-sized spherical silver-coated Cu powder fully fill the skeleton space to reduce defects such as pores, gaps, and cracks in the sintering system.

[0093] For S2 and S3, although the melting points of Cu and Ti are relatively high, a considerable part of the components in the composite Cu powder and the composite Ti powder are coated with Ag on the surface, and the slurry system also contains a lot of Ag. The melting point of Ag is relatively low. The fully melted Ag during sintering can flow to fill defects and form a film on the surface of Cu and Ti. On the first hand, it avoids the formation of many defects inside the electrode due to insufficient melting and sintering of Cu and Ti in the system after sintering. On the second hand, it effectively prevents the formation of oxide film on the surface of Cu and Ti that are not completely sintered in the system, thereby increasing the resistance. On the third hand, Ag becomes an excellent conductor between components such as Cu and Ti in the electrode system. As a connecting link between these components that are not fully melted and sintered in the electrode system, it further reduces the overall resistance of the electrode. In addition, the alloy elements used in S2 and S3 are all metals with strong conductivity, so the influence of alloy element lattice distortion and insufficient melting and sintering of Cu and Ti is still within a controllable range.

[0094] In S4-S5, as the content of Cu-Ti alloy and Ag changes, the electrical properties also change synchronously. It can be seen that when the Ag content increases, the conductive properties of the slurry will be optimized to a certain extent. Although the excessive Cu-Ti alloy content will affect the electrical properties of the electrode system to a certain extent, as mentioned above, the alloy form of Cu-Ti can be fully melted and sintered, and the electrical properties of Cu-Ti itself are relatively excellent, so the change in electrical properties caused by the change in the Cu-Ti alloy content is completely within an acceptable and controllable range.

[0095] Among D1 to D5, the overall electrical performance of D1 is relatively excellent. This is because Ag accounts for the vast majority of the slurry mass ratio. However, too high an Ag content will greatly increase the electrode cost, which is not conducive to cost reduction and efficiency improvement.

[0096] The electrical performance of D2 and D3 is much worse than that of S1 to S5, and even compared with D1, especially D3. It has been verified that the main problem is that the Cu or Ti content in D2 and D3 is too high. The melting point of Cu is 1084.6℃, and the melting point of Ti is 1668℃. It is difficult to fully sinter at a sintering temperature of 740 to 800℃. Observation of the microscopic morphology shows that a large part of the Cu powder or Ti powder in the electrode is basically not tightly connected with other components, which leads to abnormally high line resistance and contact resistance, which cannot meet the normal use requirements of xBC electrodes.

[0097] The electrical performance of D4 and D5 is better than that of D3, especially D4, whose line resistance is even better than S3. The line resistance of D5 is significantly higher than that of D1 and D2.

[0098] For D4, the main reasons are: although the Cu-Ti alloy inevitably has the problem of lattice distortion affecting the electrical properties, on the one hand, the electrical properties of the two elements Cu and Ti themselves are relatively good, and the amount of alloy additives is not much, so the impact of the alloy lattice distortion is still within the controllable range; on the other hand, the Ag content in the electrode system is relatively high, and Ag, as a very good conductor, can significantly improve the electrical properties of the electrode system; however, compared with S3, the Ag content of D4 is too high, resulting in higher costs, and the electrical properties are not significantly different in comparison.

[0099] For D5, it is obvious that the Cu-Ti alloy content in the system is too high and the Ag content is low, so the impact of lattice distortion is already very obvious.

[0100] It should be understood that although this specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each implementation mode may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

[0101] The series of detailed descriptions listed above are only specific descriptions of feasible implementation methods of the present invention. They are not intended to limit the scope of protection of the present invention. Any equivalent implementation methods or changes that do not deviate from the technical spirit of the present invention should be included in the scope of protection of the present invention.

Claims

1. An xBC battery slurry based on Ti, Cu and Cu-Ti alloy, characterized in that: include: 85-90 wt% conductive phase; Based on the total mass of the conductive phase, it includes 5-15wt% of composite Ti powder, 10-30wt% of composite Cu powder, 5-25wt% of Cu-Ti alloy powder, and 30-80wt% of Ag powder; 3-6 wt% glass phase; 0.5-3wt% auxiliary materials; The remainder is carrier.

2. The slurry according to claim 1, characterized in that The composite Ti powder is specifically a mixture of micron-sized flaky silver-coated Ti powder, micron-sized spherical silver-coated Ti powder, and nano-sized spherical silver-coated Ti powder; based on the total mass of the composite Ti powder, the content of the micron-sized spherical silver-coated Ti powder is 50-60wt%, and the content of the nano-sized spherical silver-coated Ti powder is not higher than 15wt%.

3. The slurry according to claim 1, characterized in that The composite Cu powder is specifically a mixture of micron-sized flaky Cu powder, micron-sized spherical silver-coated Cu powder, and nano-sized spherical silver-coated Cu powder; based on the total mass of the composite Cu powder, the content of the micron-sized flaky Cu powder is 30-40wt%, and the content of the nano-sized spherical silver-coated Cu powder is not higher than 5wt%.

4. The slurry according to claim 1, characterized in that The Cu-Ti alloy powder is a mixture of micron-sized spherical Cu-Ti alloy powder, micron-sized flaky Cu-Ti alloy powder and nano-sized spherical Cu-Ti alloy powder; In the Cu-Ti alloy, the content of Ti is 0.6-1.2 wt %.

5. The slurry according to claim 1, characterized in that Based on the total mass of the Ag powder, it comprises 65-70wt% of micron-sized spherical Ag powder, 25-30wt% of micron-sized flaky Ag powder and 2-5% of nanometer-sized spherical Ag powder.

6. The slurry according to claim 1, characterized in that The glass phase includes a first glass powder and a second glass powder, and according to the total mass of the glass phase: The first glass powder comprises 35-60 wt % of Bi2O3, 25-40 wt % of B2O3, and 5-20 wt % of SiO2; The mass percentage of the second glass powder is 8-12wt%; the second glass powder is a mixture of at least two of BaO, ZnO, GaO, K2O, and Na2O.

7. The slurry according to claim 1, characterized in that The auxiliary material is a mixture of WO3, metal fluoride and boron powder; based on the total mass of the auxiliary material: The content of WO3 is 30-50wt%; The metal fluoride content is 10-15wt%; The content of the boron powder is 30-45wt%; the D50 particle size of the boron powder is 1-2.5 μm.

8. The slurry according to claim 1, characterized in that The carrier includes a mixed solvent and a resin; The mixed solvent is a mixture of terpineol and butyl carbitol and / or citric acid, and the mass proportion of the terpineol is ≥60%; Based on the total weight of the carrier, the resin comprises 5-8wt% of ethyl cellulose, 0-5wt% of Span series and / or Tween series, 1.5-2.5wt% of sodium dodecylbenzene sulfonate, and 0.2-0.8wt% of polyamide.

9. The method for preparing the slurry according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1. Place terpineol in a heating container, maintain the temperature at 45° C., slowly add butyl carbitol and / or citric acid and keep stirring, stir at a stirring speed of 15 rpm for 3 to 5 minutes, so that butyl carbitol and / or citric acid are fully mixed in terpineol to obtain a mixed solvent; S2, mixing the various components of the resin evenly, keeping the mixed solvent at 45°C, adding the mixed resin to the mixed solvent, keeping the temperature at 50°C after the resin is completely added, and stirring continuously for 2.5 to 3 hours to make the resin and the mixed solvent fully mixed to form a liquid carrier with a uniform and stable texture, and cooling to room temperature for standby use; S3, adding the glass phase and Ag powder into the carrier, stirring and dispersing at a speed of 20 to 30 rpm; S4, stirring at a speed of 20 to 30 rpm, mixing the auxiliary materials and the Cu alloy powder evenly, and then adding them to the carrier, stirring continuously for 8 to 12 hours to obtain a paste; S5. Disperse the paste obtained in S4 7 to 8 times, each time for 10 to 20 minutes, to obtain the slurry.

Citation Information

Cited By

  • Functional Coating and Method of Preparation

    AU2025263904B1